Contrast-enhanced Ultrasound as a Method of Splenic Injury Assessment - Ugo Giordano; Jakub Kobialka; Joanna Bystron; Anna Dziekiewicz; Justyna Pilch; Karolina Matuszewska; Adrian Bystroń (Journal of Medical Ultrasound)
Splenic injuries are common in abdominal trauma, as the spleen is one of the most often harmed organs. The treatment of splenic injuries underwent major changes during the past decades, shifting from a surgical approach to nonoperative management. This change of the proceedings results from a constantly growing awareness of the spleen’s crucial hematological and immunological function and was possible owing to the advances in radiological techniques. In a setting of high-energy trauma in hemodynamically stable patients, computed tomography (CT) remains the gold standard. Where ultrasonography (US) is of major importance is in cases of unstable patients undergone high-energy trauma or in patients after low-energy trauma. Nevertheless, baseline US’s sensitivity is not sufficient to detect splenic traumatic injuries; hence, a new method was developed involving ultrasound contrast agents (UCAs), called contrast-enhanced ultrasound (CEUS). In a low-energy trauma setting, it facilitates the diagnosis of abdominal lesions with a sensitivity close to that of CT, without the disadvantages of the latter. In addition, CEUS can be used in the follow-up of abdominal traumatic injuries. The fact that CEUS preserves CT’s sensitivity while not carrying the risk of radiation-induced cancer makes it feasible for children and pregnant women. This review aims to discuss the technical aspects of CEUS, the limitations, and possibilities regarding this modality, present the appearance of both a healthy and injured spleen, and compare CEUS’s effectiveness to that of CT through an analysis of retrievable studies.